Cross-linguistic parallels in processing derivational morphology: evidence from Polish. - Bozic, Mirjana; Szlachta, Zanna; Marslen-Wilson, William D (Brain & Language, 2013)
Neuroimaging evidence in English suggests that the neurocognitive processing of derivationally complex words primarily reflects their properties as whole forms. The current experiment provides a cross-linguistic examination of these proposals by investigating the processing of derivationally complex words in the rich morphological system of Polish. Within the framework of a dual language system approach, we asked whether there is evidence for decompositional processing of derivationally complex Polish stems - reflected in the activation of a linguistically specific decompositional system in the left hemisphere - or for increased competition between the derived stem and its embedded base stem in the bilateral system. The results showed activation in the bilateral system and no evidence for selective engagement of the left hemisphere decompositional system. This provides a cross-linguistic validation for the hypothesis that the neurocognitive processing of derived stems primarily reflects their properties as stored forms.